Model registration: a call to action - Sampson, Christopher James; Wrightson, Tim (Springer International Publishing, 2017)
Evidence regarding the effectiveness of health technologies can be distorted via numerous mechanisms, including publication bias, methodological errors, over- interpretation of findings and fraud. In recent years, popular science writers have brought these issues to the fore, resulting in popular movements to improve the credibility of science. One particularly effective campaign has been that of the AllTrials movement, which focuses on the pre-registration and reporting of all clinical trials [1]. Many of the concerns that led to this campaign can be observed in the context of decision modelling. In 2010, researchers called for the creation of a collaborative organisation to oversee a registry of decision models [2]. The concept was not realised. In recent years, the landscape of academic publishing and collaboration has changed dramatically. In this editorial, we restate the call for a model registry and recommend actionable steps for its introduction.